A limited edition murder - Elliott, Lauren (Elliott, Lauren. Beyond the Page bookstore mystery., 2024)
Although enjoying her extended stay working at Second Chance Books and Bindery in West Yorkshire, Addie still feels adrift--far from home, her friends, and her own beloved bookstore, Beyond the Page Books and Curios. The engagement party of her dear friend, Tony, at Milton Manor promises to be a joyful distraction. But there's an ill wind blowing at the estate: When Tony presents his fiancé with a special copy of Wuthering Heights as an engagement gift, the lord of the manor insists the book was stolen from his library... Things go from troubling to tragic when Addie takes her Yorkipoo, Pippi, out for a walk on the moors and stumbles across the body of a young woman. When the police suspect Tony of foul play, Addie vows to get to the bottom of what's going on. But it's a twisted, treacherous path to the truth and Addie will need to watch her every step...